Winter crop and residue biomass potential in China. Issue 5 (September 2011) - Baxter, Ryan; Feyereisen, Gary; Yu, Yanling; Richard, Tom L
Background: To estimate the scale of bioenergy winter crops and summer crop residue opportunities in China, winter rye ( Secale cereal ) yields were predicted using RyeGro, while straw production from corn, wheat and rice was calculated using a global agricultural database.Results: Potential winter rye biomass yields ranged from 11, 099, 000 to 23, 745, 700 Mg, while summer crop residues totaled 365, 600, 000 Mg after discounting for losses and alternative uses.Conclusion: Widespread existing double-cropping systems, as well as low winter precipitation and temperatures in China''s northern regions, limit the potential to directly increase biomass production using winter crops. However, winter crop synergies can increase sustainable harvests of summer crop residues, allowing China to provide a significant fraction of its energy needs from integrated food and biomass production systems.